Evaluating Challenges and Adoption Factors for Active Assisted Living Smart Environments - Lam, Lena; Fadrique, Laura; Bin Noon, Gaya; Shah, Aakanksha; Morita, Plinio Pelegrini (Frontiers in Digital Health, 2022)
While there have been rapid advancements in individual technologies such as Internet of Things (IoT) and Active Assisted Living (AAL) to address challenges related to an aging population, there remain large gaps in how these technologies can be integrated into the broader ecosystem to support older adults in aging in place. This research provides an overview of 15 solutions available to date around the globe and compares key factors for adoption in each solution, including user acceptance, privacy and security, accessibility, and interoperability. To scale these solutions sustainably and universally, the development and implementation of standards for key factors for adoption in AAL environments is critical. There is also a need for increased and sustainable funding to complement research priorities, to continue advancing AAL technologies.